Application of inerter in passenger vehicle suspension systems / Soong Ming Foong - Soong, Ming Foong (2015)
Inerter is a suspension element with the property that the force generated at its two terminals is directly proportional to the relative acceleration between the terminals, similar to the way a spring reacts to relative displacement and a damper to relative velocity. Studies have shown the inerter’s effectiveness in providing superior performance in various suspension applications, including passive vehicle suspensions. However, presently two issues limiting its application in passenger vehicle suspensions are the non-prominent ride improvement for some studied suspension layouts such as the parallel layout using parameter values in the passenger vehicle’s range, and the practical considerations of its physical implementation. This research aims to achieve greater application of inerter in passenger vehicle suspensions by studying several changes or modifications in employing the inerter and its concept. Firstly, the interaction of parallel inerter with controllable vehicle suspension systems was studied to determine the working principle of inerter in vehicle suspensions and also to determine its effectiveness when paired with controllable suspensions. Also, the practicality of a parallel inerter implementation was studied by investigating the feasibility of an inerter incorporating damping. Then, switching algorithms were implemented to the inerter to evaluate potential further ride performance improvement brought by these modifications. Finally, a working mechanism originated from inerter was adopted in vehicle suspension to evaluate its effect on suspension characteristic. In general, the outcomes of these analyses demonstrated the applicability of inerter in passenger vehicle suspensions: in the first part, it was shown that the parallel inerter worked by cancellation with spring force to reduce total suspension force which brought ride improvement, and it was similarly effective even when paired with controllable suspension systems, giving consistent 2 % to 4 % improvement.Additionally, the practicality of parallel inerter implementation was demonstrated by the incorporation of eddy current damping in an inerter. In the second part, the use of semi-active switching algorithm on an inerter showed greater ride improvement of up to 12 % than that brought by passive inerter, while the non-linearity which was also modeled as switching law for the inerter managed better sprung mass transient response. Lastly, the analysis of vehicle suspension adopting inerter-derived mechanism demonstrated the capability of varying suspension characteristics, hence a potential of realizing semi-active suspension system for improved performance. Overall, this research shows that greater application of inerter in passenger vehicle suspensions can be achieved through the modifications to, and the derivations from, its initial concept, for example by interacting it with controllable suspension systems as in the research.